Oral administration of pyridostigmine bromide and huperzine A protects human whole blood cholinesterases from ex vivo exposure to soman - Gordon, Richard K.; Haigh, Julian R.; Garcia, Gregory E.; Feaster, Shawn R.; Riel, Michael A.; Lenz, David E.; Aisen, Paul S.; Doctor, Bhupendra P. (Chemico-biological interactions, 2005)
Cholinesterases (ChEs) are classified as acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) according to their substrate specificity and sensitivity to selected inhibitors. The activities of AChE in red blood cells (RBC-AChE) and BChE in serum can be used as potential biomarkers of suppressed and/or heightened activity in the central and peripheral nervous systems. Exposure to organophosphate (OP) chemical warfare agents (CWAs), pesticides, anesthetics, and a variety of drugs such as cocaine, as well as some neurodegenerative and liver disease states, selectively reduces AChE or BChE activity. In humans, the toxicity of pesticides is well documented. Therefore, blood cholinesterase activity can be exploited as a tool for confirming exposure to these agents and possible treatments. Current assays for measurement of RBC-AChE and serum BChE require several labor-intensive processing steps, suffer from wide statistical variation, and there is no inter-laboratory conversion between methods. These methods, which determine only the serum BChE or RBC-AChE but not both, include the Ellman, radiometric, and ΔpH (modified Michel) methods. In contrast, the Walter Reed Army Institute of Research Whole Blood (WRAIR WB, US Patent #6,746,850) cholinesterase assay rapidly determines the activity of both AChE and BChE in unprocessed (uncentrifuged) whole blood, uses a minimally invasive blood sampling technique (e.g., blood from a finger prick), and is semi-automated for high-throughput using the Biomek 2000 robotic system. To date, the WRAIR whole blood assay was used to measure AChE and BChE activities in human blood from volunteers in FDA clinical trials. In the first FDA study, 24 human subjects were given either 30 mg PB orally ( n = 19) or placebo ( n = 5). Blood samples were obtained pre-dosing and 2.5, 5, 8, and 24 h post-dosing. The samples were analyzed for AChE and BChE activity using the WRAIR WB robotic system, and for PB concentration by HPLC. We found that maximal inhibition of AChE (26.2%) and concentration of PB (17.1 ng/mL) occurred at 2.5 h post-PB dosing. AChE activity returned to almost 100% of pre-dose values by 6 h. A dose-dependent linear correlation was found between the amount of PB measured in the blood and the inhibition of AChE. Following soman (GD) exposure, recovered AChE activity was similar to levels that were reversibly protected by the PB administration. Therefore, the WRAIR ChE WB data clearly supports the conclusion that PB is an effective pre-treatment drug for nerve agent exposure (GD). In the second FDA human study for the treatment of Alzheimer's disease, the WRAIR ChE WB assay was used to determine the RBC-AChE and serum BChE profile of healthy elderly volunteers receiving Huperzine A. Huperzine A is a plant-derived reversible and selective AChE inhibitor compared to BChE, and is a more potent inhibitor of AChE than PB. Huperzine A is available as a nutraceutical, a natural supplement reported to improve memory, and has a variety of neuroprotective effects. Individuals received an increasing dose regimen of huperzine A (final dose 200 μg after 4 weeks), which produced more than 50% inhibition of RBC-AChE. Huperzine A was well tolerated by these patients at doses that sequestered more RBC-AChE than PB, and thus warrants further study as a prophylaxis for OP poisoning in addition to Alzheimer's therapy. Due to the documented use of OPs by terrorists and in warfare around the globe, Federal, State, and local authorities need a reliable, fast, inexpensive, and standard method for confirming such an assault in order to initiate appropriate containment, decontamination, and treatment measures. This assay is ideal for prescreening military personnel for atypical ChE activities that would preclude their deployment to areas of potential CWA exposure. The WRAIR WB ChE assay will fulfill the requirement for rapid and reliable monitoring of such exposure in military and civilian populations.